2017
DOI: 10.1016/j.biomaterials.2017.06.039
|View full text |Cite
|
Sign up to set email alerts
|

Decoupling the effects of stiffness and fiber density on cellular behaviors via an interpenetrating network of gelatin-methacrylate and collagen

Abstract: The extracellular microenvironment provides critical cues that guide tissue development, homeostasis, and pathology. Deciphering the individual roles of these cues in tissue function necessitates the development of physically tunable culture platforms, but current approaches to create such materials have produced scaffolds that either exhibit a limited mechanical range or are unable to recapitulate the fibrous nature of in vivo tissues. Here we report a novel interpenetrating network (IPN) of gelatin-methacryl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
110
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(114 citation statements)
references
References 64 publications
3
110
0
Order By: Relevance
“…Fibrillar collagen can be challenging to incorporate and maintain in three-dimensional matrices, because its fibers can be inhibited or altered by changes in collagen content and matrix crosslinking mode and density. Collagen type I can form interpenetrating networks with hydrogels formed with non-covalently [20] or dynamic covalently [17] crosslinked polymers, as well as methacrylated-gelatin [21]. However, none of these studies have reported that collagen fiber architecture can be maintained independent of matrix viscoelasticity.…”
Section: Introductionmentioning
confidence: 99%
“…Fibrillar collagen can be challenging to incorporate and maintain in three-dimensional matrices, because its fibers can be inhibited or altered by changes in collagen content and matrix crosslinking mode and density. Collagen type I can form interpenetrating networks with hydrogels formed with non-covalently [20] or dynamic covalently [17] crosslinked polymers, as well as methacrylated-gelatin [21]. However, none of these studies have reported that collagen fiber architecture can be maintained independent of matrix viscoelasticity.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of 3D fibrillar structures on cellular outcomes has been highlighted in recent studies in which a wide variety of tissues have been mimicked . Aligned fibers in tumors have been shown to play an important role in directing cancer cell behavior during tumor metastasis and fiber alignment can be used as a paradigm for predicting human breast cancer survival .…”
Section: Introductionmentioning
confidence: 99%
“…Tumor cells require the presence of fibers to invade the surrounding stroma . These fibers not only provide biological cues to embedded cells, but also uniquely influence cell–cell communication and alignment, in addition to the degree of cell contraction . Techniques have been developed recently to construct cell culture platforms, including microfabrication, selective laser sintering, phase separation, stereo lithography, electrospinning, fused filament fabrication, and 3D printing .…”
Section: Introductionmentioning
confidence: 99%
“…Cell fates could be determined by mechanical cues (Han et al, 2016;Wang et al, 2018a;Liu et al, 2019). The cells sense mechanical signals and secret different growth factors to control the differentiation, proliferation and migration behaviors (Berger et al, 2017;Pogoda et al, 2017). It is considered that the modulus of 18-28 kPa could induce the differentiation of stem cells to chondrocytes while the modulus of above 28 kPa would stimulate the osteo-differentiation (Engler et al, 2006;Ding et al, 2017.09).…”
Section: Perpendicular Parallelmentioning
confidence: 99%
“…Gelatin methacryloyl (Gel-MA, EFL-GM-90, Suzhou Intelligent Manufacturing Research Institute, Suzhou, China) and N-isopropylacrylamide (NIPAM, Aladdin Chemistry Co. Ltd, Shanghai, China) were chosen as the models of natural and synthetic biomaterials and blended with BSNF solution. According to previous studies (Berger et al, 2017;Gao et al, 2019), the freeze-dried Gel-MA was dissolved in lithium phenyl-2,4, 6-trimethylbenzoylphosphinate (LAP, EFL-LAP, Suzhou Intelligent Manufacturing Research Institute, Suzhou, China). The Gel-MA solution was blended with BSNF solution (2 wt%) at the volume ratio of 1:1.…”
Section: Fabrication Of Hydrogels With Gradient Cuesmentioning
confidence: 99%